2023
DOI: 10.3390/antiox12071372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sihuang Zhili Granules on the Diarrhea Symptoms, Immunity, and Antioxidant Capacity of Poultry Challenged with Lipopolysaccharide (LPS)

Abstract: A growing interest has been focused on Chinese herbs as alternatives to antimicrobial growth promoters, which are characterized by non-toxic side effects and drug resistance. The purpose of this study was to evaluate the effects of the Sihuang Zhili granule (abbreviated as Sihuang) on diarrhea, immunity, and antioxidation in poultry. Thirty male Leghorn chickens, aged 21 days, were randomly assigned to one of three groups with ten animals each. The control group (CON) received intraperitoneal saline injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It has been reported that LPS-induced immune stress may inhibit feed intake and body weight gain in broilers by inflammatory responses. Intraperitoneally injected or orally administered LPS can translocate across the intestinal barrier and enter the bloodstream, leading to activation of the TLR4 complex, up-regulating the MAPK-NF-κB signaling pathway, increasing cyclooxygenase-2 activity, resulting in the production of cytokines and chemokines, such as IL-1β, and eliciting systemic pathological change ( Page, et al, 2022 ; Liu et al, 2023 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LPS-induced immune stress may inhibit feed intake and body weight gain in broilers by inflammatory responses. Intraperitoneally injected or orally administered LPS can translocate across the intestinal barrier and enter the bloodstream, leading to activation of the TLR4 complex, up-regulating the MAPK-NF-κB signaling pathway, increasing cyclooxygenase-2 activity, resulting in the production of cytokines and chemokines, such as IL-1β, and eliciting systemic pathological change ( Page, et al, 2022 ; Liu et al, 2023 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%